Consequences of Government Expenditure Shocks with Influence from Effectiveness and Efficiency Indices on National Economic Activities: A Smooth Transition Threshold Regression (LSTAR) Approach - Salari, Abouzar; Damankeshideh, Marjan; Afsharirad, Majid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The primary objective of this study is to investigate the asymmetric effects of government current and capital expenditures on economic growth in Iran from 1994 to 2021. This research aims to understand how different levels of government spending, influenced by the indices of effectiveness and efficiency, impact national economic activities. Methodology: This study employs the Smooth Transition Threshold Regression (LSTAR) method to analyze the nonlinear relationships between government expenditures and economic growth. The data was collected from the World Bank and the Central Bank of Iran. The analysis involves determining the optimal lag using the Schwarz criterion, testing for nonlinear relationships, selecting appropriate transition variables, and estimating the model parameters. The estimation process includes examining the linear and nonlinear impacts of various variables on economic growth. Findings: The findings reveal that government current and capital expenditures have significant asymmetric effects on economic growth in Iran. In the linear section, government expenditures positively impact economic growth, while in the nonlinear section, the effects are negative. The results indicate that there is a threshold level for government spending (28.09% of GDP), beyond which the effects on economic growth become negative. Additionally, the study finds that economic corruption negatively impacts economic growth, and taxes have a negative and significant effect in both linear and nonlinear contexts. Conclusion: The study concludes that while government current and capital expenditures can stimulate economic growth through various channels, such as employment and infrastructure development, there is a critical threshold beyond which these expenditures may hinder growth. Policymakers should consider this threshold when planning and allocating government budgets to optimize the positive effects and mitigate the negative impacts. The research also highlights the detrimental effects of economic corruption and excessive taxation on growth, suggesting the need for effective anti-corruption measures and balanced tax policies